Association Between Passive Smoking and Health Among Chinese Nurses: A Cross-Sectional Study - Xia, Chun-ling; Xiao, Shi-qi; Wu, Qi-jun; Yu, Xin-ying; Xing, Lin-lin; Gai, Li; Xia, Tian-hui; Feng, Hui-ling; Zhang, Xin-ying; Guo, Ying; Xu, Yi-wei; Fu, Tong-tong; et al. (Frontiers in Public Health, 2021)
This study aimed to investigate the association between passive smoking and physical and psychological health in Chinese nurses. Participants of this cross-sectional study comprised 2 484 non-smoking nurses. Passive smoking and demographic information were assessed using a self-administered questionnaire. Physical, psychological, and overall health status of nurses were measured using the Cornell Medical Index (CMI) health questionnaire. Multivariate-adjusted odds ratio (OR) and 95% confidence interval (CI) for nurses’ health were estimated by exposure to passive smoking using unconditional logistic regression models. A total of 1219 nurses (49.07%) were exposed to passive smoking. Of these, 609 (24.52%), 160 (6.44%), and 587 (23.63%) nurses had poorer physical, mental, and overall health, respectively. After adjusting for other confounding factors, compared with the non-passive smoking group, passive smoking was associated with poor physical (OR=1.51, 95%CI: 1.25-1.83), mental (OR=1.48, 95%CI: 1.07-2.07), and overall (OR=1.58, 95%CI: 1.30-1.93) health of nurses, respectively. We also carried out subgroup analyses stratified by age, department, and professional title, which showed that most findings supported the main results. This study demonstrated that exposure to passive smoking was a risk factor for overall decreased physical and mental health status among Chinese nurses.